The synthesis and testing of novel analogues of (+)-ambuic acid as inhibitors of staphylococcal virulence - Reekes, James (2021)
Staphylococcus aureus is a Gram-positive human pathogen of significant clinical importance. The development of resistance to numerous classes of clinically important antibiotics has exacerbated the need for the development of novel therapeutic modalities for the treatment of serious, drug-resistant S. aureus infections.